END-OF-LIFE CARE PREFERENCES OF PERSONS WITH MILD COGNITIVE IMPAIRMENT/DEMENTIA AND THEIR CARE PARTNERS. (11th November 2018) - Belanger, E; Jutkowitz, E; Shepherd-Banigan, M; Van Houtven, C; Plassman, B L; Wetle, T; Mor, V
Abstract: We examined documentation of end-of-life care preferences among patients who received an Amyloid PET scan and their care partners. We used qualitative content analysis to explore 100 patients' responses to open-ended questions about how they hoped the scan would influence their future. We also asked patients and care partners whether they had discussed care preferences with healthcare providers, and had a living will or advanced directive. We estimated multivariable logistic regression models to assess the relationship between cognitive impairment, scan results and documentation of care preferences. Participants were concerned with the uncertainty of disease progression, but seldom mentioned documenting end-of-life care preferences when discussing the future. Preliminary results show that while 24.40% of patients reported having spoken with their healthcare provider, 81.40% and 72.20% had a living will and advance directives, respectively. Better cognitive function was associated with increased odds of discussing preferences with a healthcare provider.